Motivating language learners: a classroom-orientated investigation of teachers' motivational practices and students' motivation - Guilloteaux, Marie-Jose (2007)
The teachers' use of motivational strategies is generally believed to enhance student motivation, yet there is scant empirical evidence to support this claim. This classroom-oriented investigation focused on how the motivational practices of EFL teachers in South Korea related to students' L2 motivation and motivated classroom behavior. In a first phase, the motivation of over 1,300 students was measured by a self-report questionnaire, and the use of motivational strategies by 27 teachers in 20 different schools was examined with a classroom observation instrument specifically developed for this investigation, the Motivation Orientation of Language Teaching (MOLT). The MOLT scheme, along with a post hoc rating scale completed by the observer, was used to assess the teachers' use of motivational strategies. The MOLT follows the real-time coding principle of Spada and Frohlich's (1995) Communication Orientation of Language Teaching (COLT) scheme but uses categories of observable teacher behaviors derived from Dornyei's (2001) motivational strategies framework for foreign language classrooms. The results indicate that the language teachers' motivational practice is directly linked to increased levels of the learners' motivated learning behavior and their motivational state. In a second phase, three high- and three low-motivation learner groups (selected from the initial sample) were compared in order to uncover the students' interpretations and understandings of the quality of their L2 instructional contexts in relation to their motivation and motivated classroom behavior. Results based on quantitative and qualitative data (which were obtained using three new instruments specifically designed for this study) indicated that the motivational practices coexisting with different levels of motivation were woven into the contents and processes of L2 instruction and instruction in general. These contents and processes seemed to stem from teachers' and students' beliefs about what counts as learning in the L2 classroom and what is the best way to learn an L2.